Tabu search based on exact approach for protecting hubs against jamming attacks. (October 2019) - Khanduzi, Raheleh; Sangaiah, Arun Kumar
Abstract: In this paper, we consider an interdiction/protection problem on a wireless network where a defender places a set of hubs and detects the locations for deploying anti-jamming devices in order to minimize the cost of installing hubs and the energy consumption before and after jamming attacks. Moreover, the attacker's objective is to detect the locations for deploying jamming devices and disrupting the operation of a wireless network such that the energy consumption is maximized. We formulate this problem as a quadratic bi-level problem. A tabu search algorithm is implemented and tested on 48 randomly generated networks. The experimental results indicate that deploying anti-jamming devices can decrease the impact of jamming attacks. We also analyze the results in comparison with a decomposition method and two metaheuristics called the genetic algorithm and teaching learning. Numerical results show the superiority of the proposed algorithm against above-mentioned approaches regarding the execution time and accuracy.